Unpleasant Operas or French Music Drama as Heard by Corno Di Bassetto - Eduardo Valls Oyarzun (Cahiers Victoriens et Edouardiens)
The status of George Bernard Shaw as an opera critic—a position he filled under the pen-name ‘Corno Di Bassetto’ in different periodicals such as The Star and The World—has been somewhat overlooked in the canon of late Victorian journalism. However, his critique of the 1880–1890 opera performances stands alone in its own right as the most influential early modern critical discourse on music drama in the British milieu. In the wake of his early enthusiasm for Wagner—a trait that pervades his writings on music during the late 1800s but nonetheless declines with the turn of the century—Shaw’s opera criticism suggests a new theory of music drama the author applies methodically to sundry opera traditions. However, this theory changes dramatically when Shaw addresses French authors, ranging from Léo Delibes, Jules Massenet and Georges Bizet to Charles Gounod. This essay examines how Shaw’s vision of the genre changes after his development of the Life Force theory, which, in turn, compels the reader to reassess Shaw’s understanding of the French opera tradition in the late 1880s and 1890s. This probing into Shaw’s evaluation of French music drama will serve to determine its actual influence on Shaw’s opera criticism.